Activation of PAC1 Receptors in Rat Cerebellar Granule Cells Stimulates Both Calcium Mobilization from Intracellular Stores and Calcium Influx through N-Type Calcium Channels - Basille-Dugay, Magali; Vaudry, Hubert; Fournier, Alain; Gonzalez, Bruno J.; Vaudry, David (Frontiers in Endocrinology, 2013)
High concentrations of pituitary adenylate cyclase-activating polypeptide (PACAP) and a high density of PACAP binding sites have been detected in the developing rat cerebellum. In particular, PACAP receptors are actively expressed in immature granule cells, where they activate both adenylyl cyclase and phospholipase C. The aim of the present study was to investigate the ability of PACAP to induce calcium mobilization in cerebellar granule neurons. Administration of PACAP induced a transient, rapid and monophasic rise of the cytosolic calcium concentration ([Ca2+]i), while vasoactive intestinal peptide was devoid of effect, indicating the involvement of the PAC1 receptor in the Ca2+ response. Preincubation of granule cells with the Ca2+ ATPase inhibitor, thapsigargin, or the D-myo-inositol 1,4,5-trisphosphate (IP3) receptor antagonist, 2APB, markedly reduced the stimulatory effect of PACAP on [Ca2+]i. Furthermore, addition of the calcium chelator, EGTA, or exposure of cells to the non-selective Ca2+ channel blocker, NiCl2, significantly attenuated the PACAP-evoked [Ca2+]i increase. Preincubation of granule neurons with the N-type Ca2+ channel blocker, omega-conotoxin GVIA, decreased the PACAP-induced [Ca2+]i response, whereas the L-type Ca2+ channel blocker, nifedipine, and the P- and Q-type Ca2+ channel blocker, omega-conotoxin MVIIC, had no effect. Altogether, these findings indicate that PACAP, acting through PAC1 receptors, provokes an increase in [Ca2+]i in granule neurons, which is mediated by both mobilization of calcium from IP3-sensitive intracellular stores and activation of N-type Ca2+ channel. Some of the activities of PACAP on proliferation, survival, migration and differentiation of cerebellar granule cells could thus be mediated, at least in part, through these intracellular and/or extracellular calcium fluxes.